Renal Pathology in HCV Infected Patients – Report of 148 Patients and Review of the Literature - Mesquita, I (2018)
Background: Hepatitis C virus infection (HCV) is a major public health problem with a reported incidence of 3‑4 million cases per year. Renal injury secondary to HCV was initially observed in autopsy studies and later in kidney biopsies. Several types of renal disease have been recognized in association with HCV patients. Objectives: Characterize the type of renal disease found in HCV‑infected patients and established as possible relation with clinical presentation. Methods: Unicentric retrospective study of HCV patients with a renal biopsy from January 1988 to December 2015. The clinical data at biopsy time was analyzed according to histological diagnosis. Results: HCV infection was present in 148 cases. Male gender was predominant (76.7%), as was Caucasian race (79.1%). Mean age was 41.46±11.47years. Histological study of renal biopsies revealed membranoproliferative glomerulonephritis (MPGN) type 1 to be the commonest lesion encountered (37.2%), followed by proliferative glomerulonephritis (16.9%), focal segmental glomerulosclerosis (FSGS) (10.1%), and tubulointerstitial nephropathy (10.1%). Other patterns (amyloidosis, diabetic nephropathy, membranous nephropathy, IgA nephropathy) were observed. Hypocomplementaemia and cryoglobulinaemia showed correlation with MPGN diagnosis. A statistically significant correlation was observed with human immunodeficiency virus (HIV) infection and FSGS diagnosis. Amyloidosis diagnosis was associated with advanced age. No other significant correlations were found. Conclusions: Renal disease in HCV patients has a broad spectrum. No strong correlations between clinical data and pattern of renal disease have been established and it seems that is not possible to predict the renal disease based on clinical criteria alone. Renal biopsy remains the gold standard for diagnosis.